Floral Designs and their Use in Product Items - Chandhasa, Rosjana; Pattanapanithipong, Panu; RTN, Pana Tappinkorn (Journal of Ecohumanism, 2025)
This study investigated the cultural significance of the butterfly bush (Buddleja paniculata) in the construction of Thai meaning, belief, ritual, wisdom, and tradition with the goal of developing and implementing a model for a creative process to co-design related cultural capital products. The researchers synthesized the aesthetic and cultural characteristics of the butterfly bush for application to creative pattern designs and products and identified two cultural dimensions composed of meaning and belief that could be adapted into design patterns along with the flower’s colors and composition. The synthesized patterns were applied to three types of women’s bags based on an analysis of women’s bag use behaviors, and the final products were evaluated by 3 flower experts, 3 design experts, 100 customers and fabric and bag producers. The results showed high satisfaction with the representativeness, attractiveness, and usability of the fabric and bag designs. The results highlight the value of cultural capital for producing attractive goods that align with market demand and contribute to sustainable livelihoods, as well as the critical roles of consumers, designers, and producers in the collaborative design of such products.